362 Comparison of PREDICT Score to Oncotype Dx Score in Early Invasive Breast Cancer. (12th October 2021) - Frixou, M; Makaranka, S; Urquhart, G; Elsberger, B
Abstract: Aim: The PREDICT score is used to help define decisions about benefits of chemotherapy in early invasive breast cancer. With a PREDICT score of 5% or more chemotherapy should be considered, 3% to 4% is a borderline decision and less than 3% chemotherapy is not pursued. We set out to compare the PREDICT score to Oncotype Dx recurrence score (RS), which predicts chemotherapy benefit based on 21-gene breast cancer assay. Method: Data for patient and tumour characteristics, and treatment choice was collected from electronic patient records of 98 patients who had an RS score done between February 2017-September 2020. This data was then compared to the patients' PREDICT scores. Results: 98 patients were analysed with 2 excluded due to having nodal macro-metastases. Mean patient age was 53 years with an average tumour size of 27mm. 31/96 (32%) patients had a PREDICT score ≥ 5%, with 21/31 (68%) having a low RS score (<26). 57/96 (59%) patients had a PREDICT score of 3-4%, with 40/57 (70%) having a low RS score. 8/96 (8%) patients had a PREDICT score of < 3%, with 7/8 (88%) having a low RS score. Additionally, 7/8 (88%) patients in this group were pre-menopausal. Conclusions: 68% of patients in the ≥ 5% PREDICT group had a low RS score and so have avoided chemotherapy. In the 3-4% group, approximately 1 in 3 tested were shown to have a chemotherapy benefit. In the <3% group most patients were pre-menopausal, and chemotherapy was safely avoided. A bigger dataset and comparison to other health boards is required.